Answer:
∠a + ∠b + ∠c + ∠d = 360°
Step-by-step explanation:
∠a + ∠c = 180°
∠b + ∠d = 180°
Therefore, 180 + 180 = 360°
Answer:
X= 7
Z= 117
Step-by-step explanation:
Z would be 117 because on the bottom half of the equation it has to be equal to 180. It gave you 63 already and so I just took the 180 and subtracted the 63 to get 117.
2 times 2=4
multiply first equation by 2 to get
-4x+6y=12
then add to get
-4x+6y=12
<u>4x-2y=8 +</u>
0x+4y=20
4y=20
y=5
sub back
-2x+3y=6
-2x+3(5)=6
-2x+15=6
-2x=-9
x=9/2=4.5
the number to multiply by is 2
Answer:
This question requires us to change the subject of a formula. This can be achieved by following the order of operations in reverse. First, isolate the terms with our variable of interest, x:
ax - bx = z - y
Then, we take x out as it is being multiplied to both a and b:
x(a - b) = z - y
Dividing (a - b) on both sides, we get:
x = (z - y) / (a - b)
Thus, the answer is x= z-y/a-b
Step-by-step explanation: